The Role of Intercultural Communication in Building Tolerance in Dasan Tereng Village - Erdin Prasetya; Abdul Malik; Muhamad Saleh (al-Afkar, Journal For Islamic Studies, 2025)
This study was conducted in Dasan Tereng Village, which is known for upholding the value of tolerance towards differences within its community. To achieve a peaceful and harmonious life, intercultural communication is one of the important methods applied. This article aims to describe the role of intercultural communication in building tolerance in Dasan Tereng Village. The approach used in this study is a literature review with a descriptive qualitative method. Data was collected through observation, interviews, and documentation. The results of the study reveal that intercultural communication plays a crucial role in building tolerance among the people of Dasan Tereng Village. In addition to creating a peaceful atmosphere, intercultural communication also contributes to creating a harmonious social life without causing conflict.